CPAP for secondary cardiovascular prevention in obstructive sleep apnoea patients: not only one moon, but many stars. Issue 3 (15th November 2022) - Baillieul, Sébastien; Shah, Neeraj M.; Dharmasena, Rivindi; Schiza, Sophia; Testelmans, Dries; Pataka, Athanasia
While continuous positive airway pressure (CPAP) therapy has a strong evidence base for the treatment of obstructive sleep apnoea (OSA), its impact on cardiovascular comorbidity remains unclear. This journal club reviews three recent randomised controlled trials aimed to evaluate the impact of CPAP therapy in secondary prevention of cerebrovascular and coronary heart disease (SAVE trial), comorbid coronary heart disease (RICCADSA trial) and in patients admitted with acute coronary syndrome (ISAACC trial). All three trials included patients with moderate-to-severe OSA and excluded patients with severe daytime sleepiness. When CPAP was compared with usual care, they all reported no difference in a similar primary composite end-point including death from cardiovascular disease, cardiac events, and strokes. These trials faced the same methodological challenges, including a low primary end-point incidence, the exclusion of sleepy patients, and a low CPAP adherence. Therefore, caution must be taken when broadening their results to the wider OSA population. Although randomised controlled trials provide a high level of evidence, they may not be sufficient to capture the diversity of OSA. Large-scale, real-world data may be able to provide a more rounded and generalisable picture of the effects of routine clinical use of CPAP on cardiovascular morbimortality. RCTs failed to demonstrate CPAP therapy efficacy in preventing secondary major adverse cardiovascular events. Exclusion of sleepy patients and a low CPAP adherence limit their external validity. RCTs may not be sufficient to capture the diversity of OSA. https://bit.ly/3qNhUZP